Sistem Informasi Inventory dan Peminjaman Barang pada Laboratorium Program Studi Sistem Komputer - Rifky Rajendra; Kodrat Iman Satoto; Rinta Kridalukmana (Department of Computer Engineering, Engineering Faculty, Universitas Diponegoro, 2013)
Information technology development today resulted in the growing number of internet users. Easy access of the internet makes it as a media presentation of data to both individuals and institutions. It is similar with Computer System major that has taken advantage of the Internet to provide a variety of information to both academic and community service in the field of information technology. But it is still using manual method to organize and inventorydata associated with inventory and borrowing system of lab in a site. One way to ease the data organization is to design an information system that can record and organize all the data held by the Computer System.Design and Implementation phase begins with system requirement analysis. Its objection is to get a proper system specification. In design phase, Data Flow Diagram is used to represent data in a logic way. The result from design phase then implements with PHP programming language, associated with Database Management System MySQL, and Javascript to generate a dynamic web-based information system.System Information inventory and Loan goods on the laboratory computer system, has two categories of access rights, there are super admin and admin (operator), where the super admin have all permissions and the lending system inventory information communications system laboratory, while the operator is further divided into three parts ie (embedded, networking, and software engineer) where each lab has one operator and one other can notaccess that does not belong to its access. The test results and Loan Information Systems Inventory Computer Systems Laboratory, showed that all the features of the application can work well as Super Admin can see the entire menu of each Lab and can make the process of printing from any lab reports, for each lab operator can to process the data change, the process of borrowing items and returns. Using the Entity Relationship Diagram modeling system. The information systems have as many as four users on the system, which are super admin, operator Lab embedded, networking lab operator, operator Lab Engineer software.